Generalized Lagrangians and Spinning Particles - Rivas, M. (Український математичний журнал, 2001)
We show that the spin structure of elementary particles can be naturally described by the generalized Ostrogradskii Lagrangians depending on higher-order derivatives. One component of a spin is related to the rotation of a particle and the other one, caused by the dependence of a Lagrangian on the acceleration, is known as a zitterbewegung component of spin. Показано, що спінова структура елементарних частинок природно описується узагальненими лагранжіаиами Остроградського, що залежать від похідних вищого порядку. Одна компонента спіну відповідає обертанню частинки, а друга, що обумовлена залежністю лагранжіана від прискорення, відома як вібраційна (zitterbewegung) компонента.